Pemberdayaan Koperasi Syariah Komunitas Usaha Mikro Muamalat Berbasis Masjid - Khatimah, Husnul; Nuradi, Nuradi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
The purpose of this research is to find out how the entrepreneurship-based empowerment program in the Koperasi Syariah Komunitas Usaha Mikro Muamalat Berbasis Masjid (KSPS KUM3) BUMI (Bangkit Mikro Usaha) Amanah. This program is one of the flagship programs of BAZNAS Sukabumi Regency in collaboration with Baitul Mal Muamalat (BMM) which is presented in the Sukabumi community to realize the values of Islamic law in community economic activities in the form of sharia cooperatives whose loans are in the form of qardhul hasan. This study uses survey research by conducting interviews with respondents through descriptive analysis methods and qualitative approaches. The author took a sample of respondents for interviews and as many as 33 people filled out the questionnaire. The results showed that the entrepreneurship-based empowerment program at KSPS KUM3 BUMI Amanah in the form of murabahah (buying and selling); Musharaka (business cooperation); and the profit or loss ratio (profit sharing) have been determined at the beginning of the contract/agreement. This program is also supported by the existence of Education and Training for the Micro Business Community Program which is run on a mosque-based basis in every UPZ Village. The program has not shown significant results, because it is still in the process of developing members and various factors, such as the low mindset, low level of education, and easy access to conventional loans have resulted in their low interest and motivation in entrepreneurship.